Students' First Amendment Rights and Demographics: Gauging School Board Responsiveness to Student Speech Policy - Mario Sergio Torres; Virginia Collier; Homer Tolson; Tse-Yang Huang (Arizona State University, 2010)
This study examined the degree to which school boards locally modified student speech policy. Using online policy manuals provided by the Texas Association of School Boards, speech policies for 91 school districts were gathered and reviewed. The results of a chi-square statistic indicate geographical location and student enrollment were significantly related to whether school boards made changes to its speech policy. Although not surprising, the more pertinent issue becomes whether student speech should generate greater attention as schools become more diverse.